Interaksi Sosial Dalam Konteks Ekonomi: Dampaknya Terhadap Pembangunan Berkelanjutan - Rr. Aisa Kartika Puspita Dewi; Nita Puspita Dewi; Dina Rizqayanti (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This paper proposes a qualitative approach combining ethnography, and grounded theory to study social interactions in the economic context and their impact on sustainable development. Ethnography will be conducted to gain in-depth understanding of the culture, norms, and values that shape economic social interactions. Grounded theory will be used to develop new concepts based on the collected empirical data. Through this qualitative approach, the study aims to provide profound insights into the complexity of economic social interactions and their impact on sustainable development.